Adding Evidence to the Role of NEUROG1 in Congenital Cranial Dysinnervation Disorders - Dupont, J (2021)
Congenital cranial dysinnervation disorders (CCDDs) are a heterogeneous group of neurodevelopmental phenotypes caused by a primary disturbance of innervation due to deficient, absent, or misguided cranial nerves. Although some CCDDs genes are known, several clinical phenotypes and their aetiologies remain to be elucidated. We describe a 12-year-old boy with hypotonia, developmental delay, sensorineural hearing loss, and keratoconjunctivitis due to lack of corneal reflex. He had a long expressionless face, severe oromotor dysfunction, bilateral agenesis/severe hypoplasia of the VIII nerve with marked atresia of the internal auditory canals and cochlear labyrinth malformation. Trio-exome sequencing identified a homozygous loss of function variant in the NEUROG1 gene (NM_006161.2: c.202G > T, p.Glu68*). NEUROG1 is considered a causal candidate for CCDDs based on (i) the previous report of a patient with a homozygous gene deletion and developmental delay, deafness due to absent bilateral VIII nerves, and severe oromotor dysfunction; (ii) a second patient with a homozygous NEUROG1 missense variant and corneal opacity, absent corneal reflex and intellectual disability; and (iii) the knockout mouse model phenotype which highly resembles the disorder observed in humans. Our findings support the growing compelling evidence that loss of NEUROG1 leads to a very distinctive disorder of cranial nerves development.